De novo missense variants in HECW2 are associated with neurodevelopmental delay and hypotonia. Issue 2 (7th July 2016) - Berko, Esther R; Cho, Megan T; Eng, Christine; Shao, Yunru; Sweetser, David A; Waxler, Jessica; Robin, Nathaniel H; Brewer, Fallon; Donkervoort, Sandra; Mohassel, Payam; Bönnemann, Carsten G; Bialer, Martin; et al.
Abstract : Background: The causes of intellectual disability (ID) are diverse and de novo mutations are increasingly recognised to account for a significant proportion of ID. Methods and results: In this study, we performed whole exome sequencing on a large cohort of patients with ID or neurodevelopmental delay and identified four novel de novo predicted deleterious missense variants in HECW2 in six probands with ID/developmental delay and hypotonia. Other common features include seizures, strabismus, nystagmus, cortical visual impairment and dysmorphic facial features. HECW2 is an ubiquitin ligase that stabilises p73, a crucial mediator of neurodevelopment and neurogenesis. Conclusion: This study implicates pathogenic genetic variants in HECW2 as potential causes of neurodevelopmental disorders in humans.